Morphological classes and gender in ɓə́ná (Yungur) - (:unkn) unknown (My University, 2015)
This paper provides an analysis of the gender system of Ɓə́ná-Yungur (glottocode: bena1260), distinguishing noun classes proper, defined as agreement classes, from morphological classes, defined in terms of number marking on nouns. The gender system is typologically unusual in its symmetry and simplicity. Ɓə́ná-Yungur has three noun classes in the singular and the same three classes in the plural. All logically possible singular-plural pairings are attested, except one. Morphological classes are much more numerous than noun classes and they show a high degree of singular-plural polarity. We argue that many of the morphological class markers are historically stacked, and therefore that their high number does not reflect a complex proto-system. This is important, because the comparison of noun class systems is used as the main criterion for the genealogical classification of languages currently classified as Adamawa and Gur.
Keywords: African Research